Upper Structure Repairing and Strengthening to Increase Capacity and Performance of Jetty: Case Study of Indonesia Sea Highway Program in West Nusa Tenggara - Suharwanto; Dimas Tri Kurniawan (Formosa Journal of Sustainable Research, 2023)
The Indonesia Government has launched the sea highway to speed up transportation and economic deployment in Indonesia. So, each jetty shall be upgraded to use for sea highways. The small jetty should be upgraded to support Ship berthing from 3000 to 5000 DWT, that in this case studied is in West Nusa Tenggara. Improvement ability and performance of the jetty, this research will be looking for upgrading methods to get the target of repairing and strengthening that is cheaper than new re-constructing. Based on the research result, the repairing is patching and strengthening, which will be done by a CFRP as additional existing steel reinforcing. Those methods can increase jetty capacity, performance, and reduce cost